Efficiency of Zantedeschia aethiopica and Nasturtium officinale in the removal of COD and BOD5 in domestic wastewater from the Santiago Antúnez de Mayolo El Tambo Urbanization - 2021 - Blancas Torpoco, Milagros Carla (2022)
Domestic wastewater is dumped directly into the water resource affecting it, for which it is important to implement environmental control and prevention. In this research, the aim is to determine the efficiency of Zantedeschia aethiopica (Water Lily) and Nasturtium officinale (Water cress) in the removal of COD and BOD5 in the domestic wastewater of the Santiago Antúnez of Mayolo El Tambo Urbanization - 2021. To achieve the objective was to collect 36 L of domestic wastewater from the Santiago Antúnez de Mayolo El Tambo Urbanization, which were placed in three glass ponds of 35 cm x 25 cm x 25 cm, which each contained 12 liters of water ; the first pond was considered as zero treatment (T0) or control treatment, In the second pond, the Zantedeschia aethiopica (Water Lily) species was placed and it was considered as treatment one (T1) and in the third pond the Nasturtium officinale (Water Cress) species was placed and it was considered as treatment two (T2). After 31 days in the zero treatment (T0) it was obtained that the domestic wastewater from the Santiago Antúnez Urbanization of Mayolo El Tambo has a concentration of 41 mg/L of BOD5 and 72.4 mg/L of COD; In treatment one (T1) with the Zantedeschia aethiopica species (Water lily) the final concentrations of 32.1 mg/L and 68.7 mg/L of BOD5 and COD were obtained respectively; In treatment two (T2) with the species Nasturtium officinale (Water cress) the final concentrations of 39.79 mg/L and 56.5 mg/L of BOD5 and COD were obtained respectively. It can be concluded that both species were efficient in removing BOD5 and COD; the Zantedeschia aethiopica species (Water lily) obtained a removal percentage of 21.71% and 5.11% for BOD5 and COD respectively; the species Nasturtium officinale (Water cress) obtained a removal percentage of 2.95% for BOD5 and 21.96% for COD.